Republic of Serbia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2008)
High capital inflows and rising vulnerabilities underscore the importance of a comprehensive approach to ensuring stability. Standard balance sheet indicators mask a substantial build-up of exposures to exchange rate, maturity, and rollover risks. Household balance sheet risks originate from currency mismatches owing to credit euroization. The fiscal balance has a strong and significant impact on the current account in Serbia. The model is broadly able to reproduce recent economic and policy developments in Serbia. The analysis indicates that privatization can result in sizable fiscal savings.